Exploring the Influence of Viewers Engagement in Live Shopping: A Study on the Impact of Skepticism and Perceived Emotional Value on Purchase Intention - Batara, Lisa Charisa; Sugiarto, Catur (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
The primary aim of this study is to investigate how viewer engagement during live streaming shopping impacts consumer skepticism, perceived emotional value, and purchase intention. Utilizing the Structural Equation Modeling (SEM) Partial Least Squares (PLS) method, we analyzed survey data gathered from consumers actively involved in the live streaming e-commerce scene in Indonesia. .The research findings indicate significant support for the proposed hypotheses. Viewer engagement is proven to have a positive impact on consumer skepticism levels and significantly contributes to the enhancement of perceived emotional value. However, interesting findings emerge when consumer skepticism levels do not significantly influence their purchase intentions. On the contrary, perceived emotional value has a significant positive impact on purchase intention. Practical implications of this research involve expanding marketing strategies that focus on increasing viewer engagement and providing strong emotional value to encourage consumer purchase intentions during live streaming shopping sessions. This research contributes to the understanding of consumer dynamics in the context of live streaming e-commerce and provides guidance for companies to optimize customer interactions and sales outcomes.